Performing Post-Racial Asianness: K-Pop's Appropriation of Hip-Hop Culture. (2014) - Oh, Chuyun
Abstract : Drawing on theories from performance studies, dance studies, and critical race studies, this paper explores the ways in which Korean pop (K-pop)'s appropriation of hip-hop reveals a complex moment of global cultural flow. Western audience reception of K-pop is likely limited to framing K-pop either as a form of contemporary minstrelsy or a postcolonial mimicry, e.g., making fun of African American culture or a bad copy of American pop. This perspective, however, understands K-pop through the lens of American culture and only considers external signs of the performances. It fails to capture the local context in Korea, such as how and why the performers appropriate hip-hop, such as the process of embodiment and training process to learn hip-hop movement, rhythm, and styles, etc. By analyzing K-pop singer G-Dragon's (GD) music videos, this paper argues that Koreans' appropriation of American culture is neither minstrelsy nor postcolonial mimicry. K-pop's chameleonic racial and gender hybridity reveals incommensurability of contemporary Asian-ness, which I have called post-racial Asian-ness as non-racialization.